Penerapan Menejemen Risiko Pada Pengelolaan Koperasi Pegawai Republik Indonesia (KPRI) - Wibisono, Yusuf (Jurnal Ilmu Manajemen Advantage, 2019)
This study aims to examine the development of the management of the Employee Cooperatives of the Republic of Indonesia (KPRI) in Lumajang Regency. Where some cooperatives can run well and achieve achievements that can be proud of, some others are less well developed, some have problems, some KPRI are no longer active. This study uses a qualitative descriptive approach, the research method uses interview methods and documentation. Also supported by a literature review that is relevant to the subject matter. This study provides a systematic overview of the management of KPRI in Lumajang Regency as it is. From several KPRI in Lumajang Regency, there are KPRI-KPRI that can carry out their roles and functions significantly in the welfare of their members. But there are some KPRI that are not healthy and finally can not work anymore. Of the 57 KPRI who are still active as many as 46 KPRI, the remaining 11 are not active. The main contributing factor is being unable to overcome the risk of trying. Thus, managers are required to be able to implement risk management in running cooperatives, by minimizing risk, transferring risk, controlling risk and risk funding.